The Use of Orthography to Increase Young Learners’ Basic Literacy: Spelling Ability - HG Retno Harsanti (Universitas Negeri Makassar, 2020)
The mastery of literacy skills of young learners is essential and fundamental which include reading and writing. Literacy skills are closely related to cognitive abilities that provide knowledge, information, and meaning. Spelling ability is one of the essential skills in reading that must be considered. This study aims to examine the use of orthography to improve the ability to spell in reading. This study was conducted with a qualitative approach through a systematical review method with meta-synthesis as the analysis tool. Data obtained from 4 previous research articles with criteria Q1 Scopus index. The results showed that orthography could improve young learners’ spelling ability.Keywords: orthography, literacy, spelling, reading